2021
DOI: 10.1213/ane.0000000000005530
|View full text |Cite
|
Sign up to set email alerts
|

A Remote Surveillance Platform to Monitor General Care Ward Surgical Patients for Acute Physiologic Deterioration

Abstract: BACKGROUND: The traditional paradigm of hospital surgical ward care consists of episodic bedside visits by providers with periodic perusals of the patient’s electronic health record (EHR). Vital signs and laboratory results are directly pushed to the EHR but not to providers themselves. Results that require intervention may not be recognized for hours. Remote surveillance programs continuously monitor electronic data and provide automatic alerts that can be routed to multidisciplinary providers. Suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…50 Automating the processing of multiple monitors using remote surveillance is feasible and can provide highly actionable information. 51 While such systems would require complex AI models, and those remain to be developed for intraoperative use, the benefits for patient safety will be substantial.…”
Section: Prediction Of Adverse Eventsmentioning
confidence: 99%
“…50 Automating the processing of multiple monitors using remote surveillance is feasible and can provide highly actionable information. 51 While such systems would require complex AI models, and those remain to be developed for intraoperative use, the benefits for patient safety will be substantial.…”
Section: Prediction Of Adverse Eventsmentioning
confidence: 99%
“…36 An ML algorithm developed using a retrospective cohort in a UK hospital system could detect 42% of cardiac arrests or unplanned ICU admissions up to 48 hours in advance, 37 while a remote surveillance program monitoring vital sign and laboratory abnormalities in otolaryngology and ophthalmology general care ward patients generated actionable alarms at a rate unlikely to cause alarm fatigue. 38 Another group used an automated warning system for early detection of severe postpartum hemorrhage in an obstetric population. 39 While emerging studies will likely continue to show the benefits of remote monitoring systems, systems anesthesiologists need to position themselves as part of collaborative multidisciplinary teams receiving notifications of patients who are becoming critically ill outside of the ICU setting.…”
Section: Extending the Reach Of The Systems Anesthesiologist: Tele-ic...mentioning
confidence: 99%
“…Recent publications using the AlertWatch platform have shown promise for how these solutions can impact acute care. Safavi et al [22 ▪ ] utilized a version of the software to perform night hour remote surveillance and alerting on severe vital sign and lab abnormalities for postoperative patients on a ward without on-site intensivist coverage. In nearly 4000 hospital visits over 18 months, the observational study demonstrated a relatively low-alarm rate (2.6 alerts per week) with a majority of alarms (67%) leading to changes in management.…”
Section: Current State-of-the Art For Technology Platformsmentioning
confidence: 99%